Variations In Weekly Load, Training Monotony, and Strain In DBL Academy Students - Amalina, Salma; Pramono, Bayu Agung; , Muhammad; Kusuma, I Dewa Made Aryananda Wijaya; Binti Tengku Alam, Tengku Melissa Fitrah (JUARA : Jurnal Olahraga, 2024)
The objective of this study was to examine and quantitatively assess the correlation between training load, strain, and RPE adolescent basketball athletes. 10 athletes who were DBL Academy students participated in the study. selected athletes are athletes who are prepared to participate in the DBL championship on the Hoops stage. They practice 3 times in semingu for 3 weeks consisting of technical, tactical, physical, and game programs. The ANOVA and Turkey statistic tests were used to see the difference in training results per week divided into weekly training load, monotony training, and training strains, The coefficient of variation (CV) in a week represents the average CV of all players in each week considering all training sessions. The result of this study was that weekly exercise load variation increased by 21% in the first week and decreased by 3% from the second week to the third week while the coefficient of variation in the week was highest in the first week at 19% and feel stagnant by 18% in the second and third weeks. Average monotony training per week was 1.8 AU and training strain 3508.5 and any strength relation between weekly training load and training strain (r=0.990; sig. 0.000). This study concluded that exercises carried out for 3 weeks had a variety of exercises that supported an increase in exercise load per week which also increased exercise tension. Coaches are important in monitoring weekly training loads; monitoring monotony and strain training will help in preparing athletes to participate in championships optimally.